Molecular Mechanisms of Autophagy in the Cardiovascular System - Gatica, Damián (Circ Res, 2015)
Autophagy is a catabolic recycling pathway triggered by various intra- or extracellular stimuli that is conserved from yeast to mammals. During autophagy diverse cytosolic constituents are enveloped by double-membrane vesicles, autophagosomes, which later fuse with lysosomes or the vacuole in order to degrade their cargo. Dysregulation in autophagy is associated with a diverse range of pathologies including cardiovascular disease, the leading cause of death in the world. As such, there is great interest in identifying novel mechanisms that govern the cardiovascular response to disease-related stress. First described in failing hearts, autophagy within the cardiovascular system has been widely characterized in cardiomyocytes, cardiac fibroblasts, endothelial cells and vascular smooth muscle cells. In all cases, a window of optimal autophagic activity appears to be critical to the maintenance of cardiovascular homeostasis and function; excessive or insufficient levels of autophagic flux can each contribute to heart disease pathogenesis. Here we review the molecular mechanisms that govern autophagosome formation and analyze the link between autophagy and cardiovascular disease.